Kommunitäre und ‚demokratisierte’ Kulturlandschaften: Zur Frage der sogenannten ‚Amerikanismen’ in deutschen Städten - Holzner, Lutz (ERDKUNDE, 2000)
Over the past 2-3 decades, German (and other European) cities have decentralized and sprawled beyond their compact layouts of medieval city centers and 19th century industrial and residential suburbs. Much of this new outer cityscape reminds many of the ’American urban-land’ and meets with stern disapproval of city administrators, politicians, and city planning departments, as well as left and right ideologues who decry the ’bad American influence’ and a weakening of the ’Christian-occidental heritage’ of German culture. It is argued here that the new German urban-land, also called Inbetween City (Zwischenstadt) by THOMAS SIEVERTS, is not just a regrettable imitation of perhaps avoidable American ways, but rather the visual concrete result in the landscape of a fundamental change of German ideological sentiment from the traditional authoritarian top-down to a more individualistic-democratic grass-roots way of life. In the U.S., anti-urban and anti-hierarchical sentiments prevailed since the inception of the country. The Founding Fathers helped to create a ’democratized’ land as they believed that power always follows property ... and the balance of power in a society accompanies the balance of property in land (JOHN ADAMS). The Land Ordinance (1785) and Northwest Ordinance (1787) ’democratized’ the land west of the Ohio and made it an ’affordable commodity for everybody’. The multi-nucleated outer city and urban-land of modern America appears as the accomplishment of such ideological plans towards a democratic society of individuals. In Germany, on the other hand, settlement and landscape planning have always been the prerogative of authorities (kings, bishops, dictators, more recently elected officials and, more often than not, unelected bureaucrats who, ’for the benefit of the community’, created a ’communal’ settlement pattern in which centrality and hierarchy of places always played a decisive role. WALTER CHRISTALLER’s central place theory was not only a model but also a tool for both the National-Socialist regime before and during World War II and for the post-war newly created democratic regime in West Germany. It was implemented to maintain and/or create a top-down hierarchical settlement landscape that favored a communal society of managed, rather than an individualistic society of independent citizens. The recent so-called ’Americanisms’ in the new German outer cities including segregated residential districts and commercial developments of all kind, by now about 80 % of land-use in all urban land of Germany, are a reflection of a weakening of the ’communal’ ideology of yesteryear versus a more individualistic-democratic way of life of modern German society. American-like settlement developments in Germany are not superficial imitations but point towards similar ideological sentiments.